AN ANALYSIS OF FIGURATIVE LANGUAGE IN THE PICTURE OF DORIAN GRAY BY OSCAR WILDE - Santoso, Muhammad Rochmat Muchson; Iskandar, Iskandar (ELITERATE : Journal of English Linguistics and Literature Studies, 2022)
Figurative language is described as the use of words or idioms having meanings that deviate from their literal meanings. Poets use this language to state things in an unconventional way, i.e. to communicate meaning indirectly. Using the theories of Knickerbocker and Reninger, In written texts, and use of figures of speech is common. . designed to achieve aesthetic effects or beauty in order to pique the reader's attention. Because figurative language is concerned with and has an aesthetic meaning, linguistic study on figurative language is interesting. The study's initial purpose was to identify the many sorts of metaphorical language that may be found in Oscar Wilde's work "The Picture of Dorian Gray." The second purpose is to use theories from knickerbocker and reninger to linguistically evaluate meanings in figure of speech analysis in work "The Picture of Dorian Gray." As a result, the author chose an examination of figurative language in classic "The Picture of Dorian Gray" was stated in the header his qualitative research and descriptive procedures in this study. the research findings are presented in extracts from the transcript. An examination of figurative language in work him "The Picture of Dorian Gray" found 37 figurative languages, with 5 categories of figurative language. 16 metaphors selected from 37 figurative languages that dominate or feature often in study items. With 16, simile is the second highest appearance, followed by personification with 6, and exaggeration and synecdoche each with two. The figurative language discovered was linguistically evaluated utilizing Knickerbocker and Reninger's methods in understanding literature (1963) to study figurative language from its essential constituents.